Rainbow Trout (Oncorhynchus Mykiss) Intestinal Epithelial Cells as a Model for Studying Gut Immune Function and Effects of Functional Feed Ingredients - Wang, Jie; Lei, Peng; Gamil, Amr Ahmed Abdelrahim; Lagos, Leidy; Yue, Yang; Schirmer, Kristin; Mydland, Liv Torunn; Øverland, Margareth; Krogdahl, Åshild; Kortner, Trond M. (Frontiers in Immunology, 2019)
The objective of this study was to evaluate the suitability of the rainbow trout intestinal epithelial cell line (RTgutGC) as an in vitro model for studies of gut immune function and effects of functional feed ingredients. Effects of lipopolysaccharide (LPS) and three functional feed ingredients (nucleotides, mannanoligosaccharides (MOS) and beta-glucans) were evaluated in RTgutGC cells grown on conventional culture plates and transwell membranes. Permeation of fluorescently-labeled albumin, transepithelial electrical resistance (TEER) and tight junction protein expression confirmed the barrier function of the cells. Brush border membrane enzyme activities (leucine aminopeptidase (LAP) and maltase) were detected in the RTgutGC cells but activity levels were not modulated by any of the exposures. Immune related genes were expressed at comparable relative basal levels as in rainbow trout distal intestine. LPS produced markedly elevated gene expression levels of the pro-inflammatory cytokines il1b, il6, il8 and tnfa but had no effect on ROS production. Immunostaining demonstrated increased F-actin contents after LPS exposure. Among the functional feed ingredients, MOS seemed to be the most potent modulator of RTgutGC immune and barrier function. MOS significantly increased albumin permeation and il1b, il6, il8, tnfa and tgfb expression, but suppressed ROS production, cell proliferation and myd88 expression. Induced levels of il1b and il8 were also observed after treatment with nucleotides and beta-glucans. For barrier function related genes, all treatments up-regulated the expression of cldn3 and suppressed cdh1 levels. Beta-glucans increased TEER levels and F-actin content. Collectively, the present study has provided new information on how functional ingredients commonly applied in aquafeeds can affect intestinal epithelial function in fish. Our findings suggest that RTgutGC cells possess characteristic features of functional intestinal epithelial cells indicating a potential for use as an efficient in vitro model to evaluate effects of bioactive feed ingredients on gut immune and barrier functions and their underlying cellular mechanisms.